Strata Residents’ satisfaction with property management to handle Short-Term Residential Accommodation (STRA): Case Study in Majlis Bandaraya Johor Bahru (MBJB) - Yaakob, Nur Alia Fateha; Shamsudin, Zarina; Mat Radzuan, Indera Syahrul; Mohsen, Masfaliza (Research in Management of Technology and Business, 2025)
This study examines the impact of property management’s commitment in addressing challenges posed by Short-Term Residential Accommodation (STRA) in strata properties towards the resident’s satisfactions. STRA has introduced issues such as safety concerns, overcrowding, noise pollution, and the deterioration of shared facilities. the research aim to assess how housing satisfaction factors including cleanliness and maintenance services, facilities, housing environment, and safety and security are influenced by the management’s commitment to resolving these issues. Using a quantitative approach by segregating the online questionaires to 310 resident of MBJB starta properties residence and analysed using SPSS software, including Spearman’s correlation. the finding reveal that cleanliness and maintenance services are the most crucial factors contributing to resident satisfaction. this study determine that the importance of proactive and efficient property management practices in enhancing resident’s quality of life and suggest strategies for improving management approaches to address STRA-related challenges effectively